The Impact of Digital Transformation on Internal Auditing and Financial Performance of Iraqi Banks - Ali, Ahmad Hussen; Dammak, Saida (Journal of Ecohumanism, 2025)
This study investigates the extent to which regulatory systems for electronic accounting information systems, with conventional controls, are implemented in banks. The research employs a questionnaire divided into two main sections : the first section focuses on the personal characteristics of the study sample, while the second section is divided into eight themes. These themes cover the bank's commitment to deregulation of electronic accounting systems, regulatory controls on access to information, security and protection of files, documentation and development of the electronic accounting system, input and output controls, operations, and the risks associated with electronic accounting information systems. Key recommendations include improving control procedures, protecting software and hardware, and adopting clear regulations for responsibilities and powers within banks. The study underscores the importance of continuous internal audits and the development of efficient electronic accounting information systems to mitigate risks and enhance the overall performance of Iraqi private banks.